Eksistensi Grup Musik Rebana Annisa di Desa Kasikan Kecamatan Tapung Hulu Kabupaten Kampar Provinsi Riau - Indri Angriani; Nurmalinda Nurmalinda; Idawati Idawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to determine the existence of the Rebana Annisa Music Group in Kasikan village, Tapung Hulu District, Kampar Regency, Riau Province. The theories used in this research are M. Save Dagun's theory (in Gracia Destari Mujianto and Eko Raharjo, 2019: 129) and the book by Drs. Save M. Dagun with the title Philosophy of Existentialism, Rineka created 1990, with indicators namely Work Activities, Having Facts, and Efforts to Maintain Existence. The method used in this research is qualitative with data collection techniques in the form of observation, interviews and documentation. In accordance with the title, this research was conducted in Kasikan village, Tapung Hulu District, Kampar Regency, Riau Province. The subjects in this research were 10 people. The findings of this research are (i) In view of the work activities of the Annisa Tambourine Music Group in Kasikan Village, it is still well known in the village and there are still many who use this Tambourine Music Group for events in Kasikan Village, marked with the practice schedule and implementation of the music group. (ii) Having facts, this Tambourine music group is recognized for its existence by performing songs which often contain songs that have educational elements in them as well as Islamic values ​​in them. (iii) The efforts made to maintain its existence, this Tambourine music group performs at events in Kasikan villages and adapts the songs they perform for these events, inviting successors such as young people or housewives to join in becoming members of Tambourine. and increasing interest among citizens, especially women, to join in establishing other tambourine music groups, so that the existing tambourine groups in Kaksian village continue to exist.